2019
DOI: 10.1103/physrevb.100.155202
|View full text |Cite
|
Sign up to set email alerts
|

Impact of phonons and spin-orbit coupling on Auger recombination in InAs

Abstract: We extend the methodology for calculating Auger recombination from first principles to include spin-orbit interaction, which allows us to study materials in which the spin-orbit splitting and the band gap are of similar magnitude. We use this methodology to compute the direct and indirect Auger coefficients in InAs and related alloys. The direct process involves only Coulomb interaction, while the indirect process is mediated by phonons. We show how the spin-orbit split-off states allow for efficient direct Au… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
1
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2
1

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 35 publications
0
1
0
Order By: Relevance
“…Previous work on AMR in InAs found that including spin-orbit coupling did not appreciably alter the AMR rate unless the splitting was large enough to form resonant states with the band gap. [22] Given that the spin-orbit splitting in silicon is significantly smaller than the band gap, we can safely omit it from our calculations in order to reduce the computational cost without suffering any severe loss of accuracy.…”
mentioning
confidence: 99%
“…Previous work on AMR in InAs found that including spin-orbit coupling did not appreciably alter the AMR rate unless the splitting was large enough to form resonant states with the band gap. [22] Given that the spin-orbit splitting in silicon is significantly smaller than the band gap, we can safely omit it from our calculations in order to reduce the computational cost without suffering any severe loss of accuracy.…”
mentioning
confidence: 99%